2022
DOI: 10.1097/sla.0000000000005491
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Recovery and Innate Immune Homeostasis in Patients Undergoing Low-pressure Versus Standard-pressure Pneumoperitoneum During Laparoscopic Colorectal Surgery (RECOVER)

Abstract: Objective: To study the effects of intra-abdominal pressure on the quality of recovery and innate cytokine production capacity after laparoscopic colorectal surgery within the enhanced recovery after surgery program. Background: There is increasing evidence for the safety and advantages of low-pressure pneumoperitoneum facilitated by deep neuromuscular blockade (NMB). Nonetheless, there is a weak understanding of the relationship between clinical outcomes, surgical injury, postoperative immune dysfunction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…For both groups, HMGB1 and HSP70 were not significantly increased one hour and 3 days after surgery compared to before surgery. This was an unexpected finding, as several previous studies report an increase in these DAMPs after different types of surgery [ 21 , 42 44 ]. Either the expression of these DAMPs is simply not increased after breast cancer surgery, or possibly the window of increase was outside the measured timepoints.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…For both groups, HMGB1 and HSP70 were not significantly increased one hour and 3 days after surgery compared to before surgery. This was an unexpected finding, as several previous studies report an increase in these DAMPs after different types of surgery [ 21 , 42 44 ]. Either the expression of these DAMPs is simply not increased after breast cancer surgery, or possibly the window of increase was outside the measured timepoints.…”
Section: Discussionmentioning
confidence: 52%
“…It is well recognized that the early postoperative immune response is predominantly immunosuppressive [ 49 ]. Leijte et al [ 21 ] and Albers et al [ 44 ] have previously described the association between DAMPs and ex vivo cytokine production capacity. Nonetheless, the fact that the ex vivo cytokine production capacity (regarded as the capacity to elicit an inflammatory response when encountering a pathogen [ 50 ]) is nearly absent one hour after surgery has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…The application of pneumoperitoneum requires the introduction of large amounts of CO 2 gas into the abdominal cavity, and studies have shown that CO 2 pneumoperitoneum may produce hypercapnia and have immunological effects on the body [ 24 ]. Kim I. and his colleague reported that low intra-abdominal pressure during laparoscopic colorectal surgery, which means less CO 2 , preserved innated immune homeostasis and formed a valuable addition to future enhanced recovery [ 25 ]. This issue has been controversial; however, from the present study, even though pneumoperitoneum affects the immune function of the organism, its effect is less compared to an open abdominal injury.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have assessed the effects of PP levels on the quality of recovery. A laparoscopic colorectal surgery 48 and a laparoscopic nephrectomy surgery 49 study reported the quality of recovery using the QoR-40 questionnaire and found no difference between the low and standard PP strategies. Similarly, we found no significant difference in recovery quality using the PostopQRS between the low and standard PP groups in the post-anesthesia care unit, on POD1 and POD3.…”
Section: Discussionmentioning
confidence: 99%